Implicit Leadership Theory Among Malaysian Managers and its Impact on the Leader-Member Expectation Gap - Subramaniam, Anusuiya (2008)
Implicit leadership theory (ILT) examines leadership as seen by followers while other theories describe what leaders are or do. The main objective of this study is to identify ILT among Malaysian managers and the impact of the expectation gap on leader member exchange (LMX) quality and subsequently on the perception of job satisfaction and turnover intention. This study's main research question is whether the different ethnic groups in Malaysia are associated with different ILT. The relationship between leadership expectation gap and the different ethnic groups in Malaysia was examined. The effect of demographic dissimilarities (differences in ethnic background and nationality of superior and subordinate) on the subordinates' leadership expectation gap is also tested. Duration of subordinates' relationship with the superior was included as a moderating variable in the leadership expectation gap - LMX quality relationships and also in the demographic dissimilarities - leadership expectation gap relationships. LMX quality was included as the mediating variable in the leadership expectation gap - work related outcomes (job satisfaction and turnover intention) relationships. The individual subordinates who work under the supervision of Malaysian and Japanese superiors were the units of analysis. The respondents were selected from Japanese MNCs listed in the Japan-Malaysia Trade Directory Web Page and the questionnaires were posted to employees of 5 Japanese MNCs listed in this directory. Purposive sampling was used. Out of 200 distributed questionnaires, 137 were completed and usable responses. The results reveal that the different ethnic groups in Malaysia are associated with different implicit leadership theories. Several results were contrary to expectations where demographic dissimilarities did not have an effect on the subordinates' leadership expectation gap. Duration of subordinates' relationship with the superior did have moderating effects on the leadership expectation gap - LMX quality relationships, but did not have moderating effects on the demographic dissimilarities - leadership expectation gap relationships. LMX quality partially mediates the leadership expectation gap-work-related outcomes (job satisfaction and turnover intention) relationships. From the preliminary search of literature, there seems to be no study that explored the Malaysian ILT. Thus, the present study provides a first real insight into the nature of ILT among Malaysian managers. It specifical1y examined the relationship between leadership expectation gap and LMX in Malaysia and its impact on job satisfaction and turnover intention. In conclusion, this study can be a stepping stone for other researchers to embark on studies concerning ILT in the Malaysian context.